2018
DOI: 10.1108/ijsi-11-2017-0060
|View full text |Cite
|
Sign up to set email alerts
|

Multi-functional nanotechnology integration for aeronautical structures performance enhancement

Abstract: Purpose The purpose of this paper is to evaluate the applicative potentiality of functional/self-responsive materials in aeronautics. In particular, the study aims to experimentally validate the enhancement of structural performances of carbon fibers samples in the presence of nanofillers, as multi-walled carbon nanontubes or microcapsules for the self-healing functionality. Design/methodology/approach The paper opted for a mechanical study. Experimental static and dynamic tests on “blank” and modified formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…The operative deflection shapes of the composite panels are shown in Figure 11 and the modal damping value are reported in Table 5. This behavior confirms relevant results assessed during previous studies conducted by the authors that already showed an increase of up to about 3.5% of modal damping compared to a standard epoxy formulation [44]. The achieved results are surely widely demonstrative of the nanotubes efficiency.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The operative deflection shapes of the composite panels are shown in Figure 11 and the modal damping value are reported in Table 5. This behavior confirms relevant results assessed during previous studies conducted by the authors that already showed an increase of up to about 3.5% of modal damping compared to a standard epoxy formulation [44]. The achieved results are surely widely demonstrative of the nanotubes efficiency.…”
Section: Resultssupporting
confidence: 89%
“…The major drawback in this case would be the unwanted reduction of elastic properties of the overall final composite. Previous research also demonstrated that noise and vibration control in aerospace composite structures can be favored with the use of nanotechnology [41,42,43,44,45]. This paper aims to develop structural composite materials with embedded integrated acoustic dumping functionality.…”
Section: Introductionmentioning
confidence: 99%
“…can be integrated into the materials/structures by exploiting the intrinsic electrical characteristics of the materials. Furthermore, the incorporation of nanostructured forms of carbon in polymeric matrices can simultaneously enhance not only the electrical conductivity and self-responsive smart functions, but also other desirable properties, such as thermal resistance, flame resistance, and durability [62,63,64,65,66,67,68,69].…”
Section: Introductionmentioning
confidence: 99%
“…Nanofilled epoxy resins are unique with respect to other materials for their tailorability and the broad range of properties and related applications. They can be designed to have many distinct properties that may be exploited to develop the next generation of functional or self-responsive materials [21,22,23,24,25,26,27,28,29,30,31]. In particular, thermosetting resins filled with specific nanostructured particles can be manufactured to manifest enhanced mechanical, acoustic, electrical, and flame-resistance properties [25,32,33].…”
Section: Introductionmentioning
confidence: 99%